The Impact of Supply Chain Integration on New Product Development Performance: Evidence from Turkish Manufacturing Industry - KOC, Erdinc; Ulaş, Dilber; Çalipinar, Hatice (International Journal of Supply Chain Management, 2018)
This study researches the relation between supply chain integration and new product development. Supply chain integration has been included in the study under three sub-dimensions: customer integration, supplier integration and internal integration. The relation between supplier integration, customer integration and internal integration and new product development has been examined separately. Gathered data received from 390 mid-sized and macro firms engaged in manufacturing industry in Ankara and Istanbul, reliability analysis and construct validity tests, content, convergent, discriminant, nomological validity and confirmatory factor analysis test results have been presented. Finally, the research model was tested through using structural equation modeling. Study findings suggest that customer integration, supplier integration and internal integration has a positive impact on new product development.